Krisis Etika Komunikasi di Media Sosial: Analisis Multidisipliner terhadap Peran Algoritma, Literasi Digital, dan Regulasi dalam Mewujudkan Ruang Publik Digital yang Bertanggung Jawab - Amril; Sazali, Hasan (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This The crisis of communication ethics in social media is a complex and systemic contemporary phenomenon, triggered by weak digital literacy, neglect of netiquette, and the dominance of digital platform algorithms. This article analyzes in a multidisciplinary manner how digital structure, virality culture, and lack of regulation contribute to the rise of hate speech, the spread of hoaxes, and aggressive communication behavior in the digital public space. Through a qualitative approach and observation of the platforms TikTok, Instagram, and X (Twitter), this study found that destructive communication behaviors do not stand alone, but rather reinforce each other in a permissive digital ecosystem. The algorithm amplifies extreme content for the sake of emotional engagement, while users are accustomed to social validation that encourages expression, without reflection. Weak regulations and low digital ethics education have also exacerbated this condition. Therefore, this article recommends integrative strategies in the form of algorithmic resistance, regulatory reform, and strengthening digital ethical literacy based on collaboration between governments, platforms, academics, and civil society. With this holistic approach, it is hoped that the digital space can become more ethical, inclusive, and responsible as a representation of modern communication civilization.